Criminology, gender and security in the Australian context: Making women's lives matter - Walklate, Sandra (Theoretical criminology, 2019)
This article examines how it might be possible to make women's lives matter in contemporary criminological understandings of security. In doing so it considers the conceptual complexity of security, and reflects on the criminological engagement with that complexity and the feminist contribution to it paying particular attention to current concerns with everyday security. The article deploys the contemporary Australian policy agenda on family violence to illustrate the paradoxes to be found within these current pre-occupations. Drawing on feminist informed work that situates violence against women within the conceptual framework of everyday terrorism, it concludes by offering further consideration to the meaning of everyday security and the implications that this has for contemporary criminological concerns with security.